2004
DOI: 10.1001/archinte.164.10.1084
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of 2 Years of Intense Exercise on Bone Density, Physical Fitness, and Blood Lipids in Early Postmenopausal Osteopenic Women

Abstract: General purpose exercise programs with special emphasis on bone density can significantly improve strength and endurance and reduce bone loss, back pain, and lipid levels in osteopenic women in their critical early postmenopausal years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
161
1
30

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(201 citation statements)
references
References 27 publications
9
161
1
30
Order By: Relevance
“…The significant increase of aerobic capacity in J and OJ groups showed that the prescribed exercise intensity and duration of 30 minutes per day, 3 times per week for 8 weeks in the present study was adequate for improving aerobic capacity of the participants. The present beneficial effect of exercise alone on aerobic capacity was in agreement with several other previous studies (Fisher et al, 2015;Kemmler et al, 2004;Suter et al, 1994). Fisher et al (2015) reported that moderate intensity exercise is more effective to improve cardiovascular fitness than high intensity training.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The significant increase of aerobic capacity in J and OJ groups showed that the prescribed exercise intensity and duration of 30 minutes per day, 3 times per week for 8 weeks in the present study was adequate for improving aerobic capacity of the participants. The present beneficial effect of exercise alone on aerobic capacity was in agreement with several other previous studies (Fisher et al, 2015;Kemmler et al, 2004;Suter et al, 1994). Fisher et al (2015) reported that moderate intensity exercise is more effective to improve cardiovascular fitness than high intensity training.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, sedentary lifestyles with lack of exercise, smoking and having high blood cholesterol level can increase one susceptibility of getting heart diseases (McArdle et al, 2010). Performing higher physical activity or aerobic exercise alone has been proven to increase cardiovascular fitness (Kemmler et al, 2004;Suter et al, 1994) and improve lipid profile (Isler et al, 2001;Kannan et al, 2014). Performing exercise can also improve antioxidant adaptation (Goon et al, 2009;Onur et al, 2011) and reduce oxidative damage markers (Goon et al, 2009).…”
mentioning
confidence: 99%
“…A 6-month resistive training program has been shown to increase muscle mass and improve BMD in the femoral region in healthy young and older adults (Ryan et al 2004). The beneficial effects of resistive or aerobic exercises on bone health in the femoral region have been reported in other studies [68][69][70][71][72]. So far, no study has been conducted to examine the effects of different forms of exercise training on bone health and soft tissue composition in individuals with stroke.…”
Section: Discussionmentioning
confidence: 89%
“…Mechanical loading is essential to maintain bone mineral [17]. Regular skeletal-loading exercise is an effective intervention to improve bone health in older healthy individuals [18,19,20,21,22]. However, little is known about the response of bone geometry to exercise in people with stroke.…”
Section: Introductionmentioning
confidence: 99%